Inconclusive Syphilis Results: A Retrospective Review of Public Health Results - Patrick O’Byrne; Leslie Tilley; Dara Spatz Friedman; Lauren Orser (Canadian Journal of Infectious Diseases and Medical Microbiology)
In the context of increasing syphilis incidence in many Western countries, we sought to better understand the frequency and outcomes associated with inconclusive serologic syphilis results. To accomplish this, we reviewed all inconclusive results that arose from an indeterminant confirmatory treponemal screen (specifically the Treponema pallidum particulate agglutination test), which were reported to Ottawa Public Health from January 1, 2019, through December 31, 2019. Our case review identified that 52 persons generated such test results during the study period, of whom 44.4% were cases requiring treatment, 46.3% were persons without new risk factors or symptoms of syphilis who had been previously treated for this infection, and 9.3% were not syphilis. Overall, these untreated syphilis cases accounted for 8.6% of all new syphilis diagnoses in our local jurisdiction during the study period. These results highlight that case investigation and prompt management of inconclusive syphilis results is an appropriate public health and clinical approach and that such a strategy could contribute to efforts to reduce increasing syphilis incidence.